Preparation method of quartz sand

By using the hydrolysis reaction of chlorosilanes, silicates and water and the gel calcination process, the problem of low quartz sand yield was solved, and high-purity quartz sand was prepared at low cost and high efficiency to meet the needs of high-end applications.

CN121377048APending Publication Date: 2026-01-23HUALU ENG & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511723596.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-21
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing chemical synthesis methods for preparing quartz sand have low yields, resulting in high production costs and making it difficult to meet the needs of high-end applications.

Method used

HCl and SiO2 nanoparticles are generated by the hydrolysis reaction of chlorosilanes, silicates and water. The pH value is adjusted to form a gel, which is then dried and calcined to obtain quartz sand. The thermodynamic and kinetic processes are controlled to improve the yield and reduce the cost.

Benefits of technology

This technology enables the low-cost and high-efficiency preparation of high-purity quartz sand, meeting the needs of high-end applications, reducing production costs, and increasing the preparation yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377048A_ABST
    Figure CN121377048A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of quartz sand. The preparation method of the quartz sand comprises the following steps: 1) mixing chlorosilane, silicate ester and water for hydrolysis reaction to generate hydrolysate containing HCl and SiO2 nanoparticles; 2) adding alkali liquor into the hydrolysate to enable the pH value of the system to reach 8.5-11 to form gel; according to the method, HCl and SiO2 nano particles are generated through preferential hydrolysis of chlorosilane, the HCl serves as a catalyst to be used for silicate ester hydrolysis, the SiO2 nano particles serve as crystal nucleuses of silicate ester sol-gel, and low-cost and high-efficiency preparation of the quartz sand is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of inorganic non-metallic materials, in particular to a preparation method of quartz sand. BACKGROUND

[0002] As an important basic industrial raw material, the application of quartz sand has been expanded from the traditional glass, ceramics and building materials fields to optical fiber, semiconductor devices, photovoltaic silicon materials and other high-tech industries. With the rapid development of electronic information industry and new energy industry, the demand for high-purity and high-quality quartz sand continues to grow, and higher requirements for the uniformity and stability of its physical and chemical properties have been put forward, which has promoted the continuous progress of quartz sand preparation technology.

[0003] To meet the extreme pursuit of quartz sand purity for high-end applications, chemical synthesis method, as a technology path that can accurately control the composition and structure of the product, has become an important research direction for preparing high-purity quartz sand. However, at present, the preparation yield of quartz sand by chemical method is generally low, which directly leads to high production cost of quartz sand, limits the competitiveness of chemical synthesis method in the market of bulk and low-cost quartz sand products, and hinders the popularization and application of synthetic quartz sand in a wider field.

[0004] Therefore, effectively improving the overall process yield of quartz sand chemical synthesis has become the key to ensuring the stable supply of quartz materials. SUMMARY

[0005] The present application provides a preparation method of quartz sand, which realizes the technical effect of low-cost and high-efficiency synthesis of quartz sand.

[0006] The present application provides a preparation method of quartz sand, which includes the following steps:

[0007] 1) mixing chlorosilane, silicate and water to carry out hydrolysis reaction, to generate a hydrolysis solution including HCl and SiO2 nanoparticles;

[0008] 2) adding lye to the hydrolysis solution to make the pH value of the system reach 8.5-11, to form a gel;

[0009] 3) drying the gel to obtain a SiO2 loose body;

[0010] 4) calcining the loose body to obtain quartz sand.

[0011] The preparation method as described above, wherein the chlorosilane includes at least one of silicon tetrachloride, trichlorosilane, dichlorodisilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, hexachloroethyldisilane and methylhydrodichlorosilane.

[0012] The preparation method as claimed in any one of the preceding embodiments, wherein the silicate comprises at least one of methyltrimethoxysilane, methyltriethoxysilane, methylorthosilicate, ethylorthosilicate, propylorthosilicate, butylorthosilicate, amylorthosilicate, isopropylorthosilicate, isobutylorthosilicate, isoamylorthosilicate, dimethylorthosilicate, diethylorthosilicate and diisopropylorthosilicate.

[0013] The preparation method as claimed in any one of the preceding embodiments, wherein the molar ratio of the chlorosilane, the silicate and the water is 0.1-5:1-10:1-30, the reaction temperature is 40-90℃, the pressure is 0-0.5MPaG, the time is 1-5h, and the stirring rate is 50-400rpm.

[0014] The preparation method as claimed in any one of the preceding embodiments, wherein the step 1) further comprises adding a surfactant to the hydrolysis solution.

[0015] The preparation method as claimed in any one of the preceding embodiments, wherein the alkali solution comprises at least one of ammonia, pyridine, ammonium carbonate solution and ammonium bicarbonate solution; and / or,

[0016] The preparation method as claimed in any one of the preceding embodiments, wherein the dropping rate of the alkali solution is 0.5-5kg / min, the temperature is 40-90℃, and the stirring rate is 50-400rpm.

[0017] The preparation method as claimed in any one of the preceding embodiments, wherein the drying temperature of the gel is 20-150℃, the pressure is -0.1-0.1MPaG, and the time is 5-20h.

[0018] The preparation method as claimed in any one of the preceding embodiments, wherein the calcining in the step 4) comprises a first-stage calcining and a second-stage calcining performed in sequence, the first-stage calcining is performed at 300-600℃ in air for 10-20h, and the second-stage calcining is performed at 800-1600℃ in HCl for 10-50h.

[0019] The preparation method as claimed in any one of the preceding embodiments, wherein the surfactant comprises at least one of PEG, Tween, fatty alcohol polyoxyethylene ether and propylene glycol monooleate.

[0020] The preparation method as claimed in any one of the preceding embodiments, wherein the second-stage calcining further comprises introducing an inert gas.

[0021] The preparation method of the quartz sand provided by the present application, by mixing chlorosilane, silicate and water to perform a hydrolysis reaction, a hydrolysis solution comprising HCl and SiO2 nanoparticles is generated; then an alkali solution is added to the hydrolysis solution, so that the pH value of the system reaches 8.5-11, a gel is formed; then the gel is dried to obtain a SiO2 loose body; finally, the loose body is calcined to obtain the quartz sand, achieving the effect of low cost and high efficiency in preparing the quartz sand. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 Gel particle size chart for Example 1 of the quartz sand preparation method of the present application;

[0023] Figure 2 Gel particle size chart for Example 2 of the quartz sand preparation method of the present application;

[0024] Figure 3 Gel particle size chart for Example 3 of the quartz sand preparation method of the present application;

[0025] Figure 4 Gel particle size chart for Example 4 of the quartz sand preparation method of the present application;

[0026] Figure 5 Gel particle size chart for Example 5 of the quartz sand preparation method of the present application;

[0027] Figure 6 Gel particle size chart for Example 6 of the quartz sand preparation method of the present application;

[0028] Figure 7 Gel particle size chart for Comparative Example 1 of the quartz sand preparation method of the present application;

[0029] Figure 8 Gel particle size chart for Comparative Example 2 of the quartz sand preparation method of the present application;

[0030] Figure 9 Gel particle size chart for Comparative Example 3 of the quartz sand preparation method of the present application. DETAILED DESCRIPTION

[0031] In order to make the objects, technical solutions and advantages of the present application clearer, the following will combine the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0032] High-purity quartz, as a strategic emerging material, is widely used in photovoltaic, electronic, optical and other cutting-edge fields. In recent years, with the rapid development of photovoltaic, semiconductor and optical industries, the market demand for high-purity quartz sand continues to grow. However, the natural high-quality quartz mineral resources are limited, and with large-scale mining, the reserves are becoming exhausted. Synthetic quartz technology breaks away from the dependence on natural ores, and uses mature and easily available bulk chemicals as raw materials to synthesize high-purity quartz sand, whose purity can even far exceed that of natural quartz sand.

[0033] At present, the liquid phase synthesis method such as chlorosilane hydrolysis method or silica sol-gel method is more used in the industry to synthesize quartz sand, and these methods have high production cost, low preparation yield and poor product density in practical application. The inventors have studied this and believe that the high production cost is mainly because a large amount of HCl gas is generated in the chlorosilane hydrolysis process, which needs to be specially collected or neutralized and treated, resulting in a complex process flow and high energy consumption; the silica ester needs to be additionally added with an acid catalyst to accelerate the hydrolysis reaction in the sol-gel process, resulting in the need to treat waste acid in the subsequent process and increasing the production cost. Further, the inventors believe that the reason for the low preparation yield is that the silica ester hydrolysis-gel process takes a long time and the product yield is limited. Under the influence of the above factors, the traditional quartz sand preparation method is difficult to meet the current market demand for high-quality quartz. Therefore, developing a low-cost and high-efficiency method for preparing quartz sand has become the key to ensuring the stable supply of quartz materials.

[0034] Based on this, the application provides a preparation method of quartz sand, comprising the following steps:

[0035] 1) mixing chlorosilane, silica ester and water to perform a hydrolysis reaction to generate a hydrolysis liquid comprising HCl and SiO2 nanoparticles;

[0036] 2) adding lye to the hydrolysis liquid to make the pH value of the system reach 8.5-11 to form a gel;

[0037] 3) drying the gel to obtain a SiO2 loose body;

[0038] 4) calcining the loose body to obtain quartz sand.

[0039] The application generates a hydrolysis liquid comprising HCl and SiO2 nanoparticles by mixing chlorosilane, silica ester and water to perform a hydrolysis reaction, and the chlorosilane is preferentially hydrolyzed to generate HCl and SiO2 nanoparticles in the hydrolysis process. HCl can promote the hydrolysis-polycondensation of silica ester as an acidic catalyst, and SiO2 nanoparticles can accelerate the formation of a gel network as a crystal nucleus. By adding lye to the hydrolysis liquid to adjust the pH of the system to 8.5-11 to form a gel, the pH range can ensure that the polycondensation rate of the silica ester hydrolysis product matches the gelation kinetics, avoiding local over-concentration or unreacted areas caused by premature gelation. The gel is dried to obtain a SiO2 loose body, and the gradient evaporation of water in the gel is realized through thermodynamic equilibrium, avoiding cracking or abnormal porosity caused by rapid drying. The loose body is calcined to obtain the final product quartz sand through the synergistic control of thermodynamics and kinetics. After the above steps, the production cost of quartz sand can be effectively reduced, and the preparation yield is improved, meeting the current market demand for high-quality quartz.

[0040] The present application does not limit the chlorosilane, and in one specific embodiment, the chlorosilane includes at least one of silicon tetrachloride, trichlorosilane, dichlorosilane, methyltrichlorosilane, dimethyldichlorosilane, chlorotrimethylsilane, hexachlorodisilane, and methylhydrodichlorosilane. Exemplarily, silicon tetrachloride, methyltrichlorosilane, and chlorotrimethylsilane are combined, which have high hydrolysis activity and moderate byproduct HCl concentration, and can be directly used as an acidic catalyst for hydrolysis of silicate without additional addition of strong acid. Among them, the HCl concentration (theoretical value about 36.5%) generated by the hydrolysis of silicon tetrachloride matches the acidity (pH 2-4) required for the hydrolysis of silicate, while the hydrolysis product (methanol) of methyltrichlorosilane can assist the dispersion of silicate as a solvent, thereby improving the uniformity of the gel. In addition, the introduction of chlorotrimethylsilane can adjust the surface hydrophobicity of SiO2 nanoparticles, reducing the agglomeration tendency during gelation.

[0041] Further, the silicate includes at least one of methyltrimethoxysilane, methyltriethoxysilane, methylorthosilicate, ethylorthosilicate, propylorthosilicate, butylorthosilicate, pentylorthosilicate, isopropylorthosilicate, isobutylorthosilicate, isoamylorthosilicate, dimethylorthosilicate, diethylorthosilicate, and diisopropylorthosilicate. Exemplarily, methylorthosilicate and ethylorthosilicate are used in combination, which have moderate hydrolysis rate and can be coordinated with the hydrolysis process of chlorosilane, avoiding local over-concentration or gel rupture caused by too fast hydrolysis of silicate. For example, the hydrolysis product of ethylorthosilicate, ethanol, can be used as a co-solvent to reduce the viscosity of the system and promote the uniform growth of the gel network; and the introduction of methylorthosilicate can adjust the surface charge density of SiO2 nanoparticles, enhancing the interfacial interaction with the hydrolysis product of silicate, thereby improving the gel strength.

[0042] In one specific embodiment, the molar ratio of chlorosilane, silicate, and water is 0.1-5:1-10:1-30, the reaction temperature is 40-90°C, the pressure is 0-0.5 MPaG, the time is 1-5 h, and the stirring rate is 50-400 rpm. The molar ratio range is determined by thermodynamic calculation: the molar ratio of chlorosilane to water needs to satisfy complete hydrolysis (theoretical value 1:2), and the molar ratio of silicate to water needs to ensure that the hydrolysis degree is ≥95%. For example, when chlorosilane:silicate:water = 1:2:4, the HCl concentration in the hydrolysis solution is about 1 mol / L, which can effectively catalyze the hydrolysis of silicate. The selection of reaction temperature is based on the Arrhenius equation: the hydrolysis rate constant k ≈ 0.05 min -1 at 40°C, and k ≈ 0.2 min -1 at 90°C, and the temperature interval can ensure that the chlorosilane is fully hydrolyzed without thermal decomposition. The stirring rate is controlled at 50-400 rpm, and the Reynolds number Re = ρND 2 / p = density of hydrolysis solution, N = rotational speed, D = diameter of paddle, p = viscosity) to ensure the system is in a turbulent flow state (Re > 10 4 ), to ensure the entire system is in a uniform concentration state.

[0043] It should be noted that step 1 also includes adding a surfactant to the hydrolysis solution. The surfactant promotes uniform dispersion of chlorosilane and silicate by reducing the surface tension of the hydrolysis solution, reducing micro-phase separation caused by differences in interfacial tension. In addition, the hydrophobic segment of the surfactant can be adsorbed on the surface of the SiO2 nanoparticles, inhibiting their agglomeration, resulting in a more uniform gel particle size distribution.

[0044] Specifically, the alkali solution includes at least one of ammonia, pyridine, ammonium carbonate solution, and ammonium bicarbonate solution. The selection of the alkali solution is based on its buffering capacity: ammonium carbonate solution (pKa ≈ 10.3) can provide a wide pH buffering range (8.5-11) to maintain a stable alkaline environment during the reaction. Ammonia (pKa ≈ 9.25) can provide a mild and stable alkaline environment for the system through its NH4 + / NH3 buffer pair.

[0045] In addition, the alkali solution is added at a rate of 0.5-5 kg / min, the temperature is 40-90°C, and the stirring rate is 50-400 rpm. For example, under the conditions of 50°C and 300 rpm, the ammonium carbonate solution is added at a rate of 1 kg / min to pH 9.2, which can effectively shorten the gelation time and avoid gel structure defects caused by pH fluctuations.

[0046] The present application does not limit the gel particle size, and in one specific embodiment, the gel particle size is 5-250 pm, where 5 pm is the minimum gel particle size and 250 pm is the maximum gel particle size.

[0047] In addition, the drying temperature of the gel is 20-150°C, the pressure is -0.1-0.1 MPaG, the time is 5-20 h, and the drying method of the gel is air drying. The thermodynamic control of the drying process is based on the Clausius-Clapeyron equation: an increase in temperature can accelerate water evaporation, and reasonable temperature control can avoid thermal stress cracking of the gel skeleton. For example, drying at 100°C under normal pressure for 12 h can significantly reduce the water content of the gel. Negative pressure (-0.1 MPaG) drying can reduce the water vapor partial pressure and promote water diffusion.

[0048] It is to be noted that in step 4), the calcination includes a first stage calcination and a second stage calcination, the first stage calcination is performed at 300-600℃ for 10-20h in air, and the second stage calcination is performed at 800-1600℃ for 10-50h in HCl. The first stage calcination removes organic matters (e.g. unreacted silicate, surfactant) and combined water (–OH group) by pyrolysis, and the temperature thereof is higher than the decomposition temperature of the organic matters (e.g. methanol is decomposed into CO2 and H2O at 300℃). The second stage calcination is performed in HCl atmosphere, and the hydroxyl content of the quartz sand is reduced by dehydroxylation reaction (Si-OH + HCl → Si-Cl + H2O) and grain recrystallization, and the densification is achieved by grain boundary migration (GBM) mechanism.

[0049] Specifically, the surfactant includes at least one of PEG, Tween, fatty alcohol polyoxyethylene ether, and propylene glycol monooleate. The molecular weight (400g / mol) of PEG matches the hydrolysis kinetics of silicate, and the hydrophobic segment (–CH2CH2O–) of PEG can be adsorbed on the surface of SiO2 nanoparticles to form steric hindrance to inhibit agglomeration. For example, the addition of 0.5wt% PEG can effectively optimize the particle size distribution of the gel, and improve the compressive strength of the quartz sand after calcination.

[0050] Based on further research of the inventor, it is found that the second stage calcination further includes the introduction of inert gas. The introduction of inert gas (e.g. argon, helium) can reduce the oxidizing property of the HCl atmosphere, and prevent the SiO2 on the surface of the quartz sand from being oxidized into SiO2·nH2O. For example, the calcination in HCl-Ar mixed atmosphere can further reduce the surface hydroxyl content of the quartz sand, and enhance the heat transfer efficiency by gas convection to shorten the calcination time.

[0051] Hereinafter, the present application is further described through specific examples.

[0052] Example 1

[0053] The present example provides a preparation method of quartz sand, including the following steps:

[0054] 1) 30kg of silicon tetrachloride, 60kg of methyl orthosilicate, 75kg of water, and 0.825kg of PEG are added into a reaction kettle, heated to 55℃, the pressure is 0.25MPaG, and stirred at 300rpm for 4 hours until the silicon source is completely hydrolyzed to obtain a hydrolysis solution;

[0055] 2) The ammonium carbonate solution is added into the hydrolysis solution at a rate of 1kg / min at 50℃ and 300rpm, so that the pH value of the system reaches 9.2, and the hydrolysis solution is gelled to obtain a SiO2 gel.

[0056] 3) The SiO2 gel is dried at 100℃ under normal pressure and blast for 12h to obtain a SiO2 loose body.

[0057] 4) The SiO2 loose body is calcined at 500℃ for 10h in air and then at 1000℃ for 30h in HCl-Ar atmosphere to obtain a high-density and low-hydroxyl synthetic quartz block.

[0058] 5) The synthetic quartz block is crushed by a pair of rollers and sieved by a rotary vibrating screen to obtain a synthetic quartz sand with a particle size of 70-200 mesh.

[0059] Example 2

[0060] The preparation method of this example is basically the same as that of Example 1, except that the chlorosilane in step 1) is trimethylchlorosilane.

[0061] Example 3

[0062] The preparation method of this example is basically the same as that of Example 1, except that the silicate in step 1) is tetraethyl orthosilicate.

[0063] Example 4

[0064] The preparation method of this example is basically the same as that of Example 1, except that no PEG is added in step 1).

[0065] Example 5

[0066] The preparation method of this example is basically the same as that of Example 1, except that the alkali solution in step 2) is ammonia.

[0067] Example 6

[0068] The preparation method of this example is basically the same as that of Example 1, except that the second-stage calcination in step 4) is carried out in an HCl atmosphere.

[0069] Comparative Example 1

[0070] The preparation method of this example is basically the same as that of Example 1, except that no chlorosilane is added in step 1), i.e., 87kg of methyl orthosilicate, 75kg of water, and 10L of 1mol / L hydrochloric acid are added to the reaction kettle.

[0071] Comparative Example 2

[0072] The preparation method of this example is basically the same as that of Example 1, except that no silicate is added in step 1), i.e., 97kg of silicon tetrachloride and 75kg of water are added to the reaction kettle.

[0073] Comparative Example 3

[0074] The preparation method of the comparative example is basically the same as that of example 1, except that no silicate is added in step 1), and the chlorosilane is trimethylchlorosilane, i.e. 62 kg of trimethylchlorosilane and 75 kg of water are added into the reaction kettle.

[0075] Test example 1

[0076] The sol-gel efficiency of the examples and comparative examples is tested, and the results are shown in Table 1:

[0077] 1) Calcined sand yield: calcined sand yield % = (m / ((chlorosilane / M1 + silicate / M2) * 60)) * 100%, wherein M1 and M2 are the molecular weights of chlorosilane and silicate, respectively;

[0078] 2) Hydrolysis time: the faster the hydrolysis, the shorter the hydrolysis time, and the higher the overall sol-gel efficiency. The end of hydrolysis is determined by chromatographic analysis system with unchanged raw material content;

[0079] 3) Gel particle size: the gel particle size is observed by scanning electron microscopy, as shown in Figure 1 、 Figure 2 、 Figure 3 、 Figure 4 、 Figure 5 、 Figure 6 、 Figure 7 、 Figure 8 、 Figure 9

[0080] 4) Bulk density: the determination method is carried out according to GB / T 21354-2008 "General method for determination of tap density of powder products".

[0081] Table 1

[0082]

[0083] As can be seen from the above table, the use of the technical scheme of the present application can significantly improve the utilization rate of silicate, and at the same time, the low-value chlorosilane is utilized, improving the economic efficiency and environmental protection of the overall process.

[0084] Finally, it should be noted that: the above examples are only used to illustrate the technical scheme of the present application, but not to limit it; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that: it can still modify the technical scheme recorded in the foregoing examples, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical scheme deviate from the scope of the technical scheme of the embodiments of the present application.​

Claims

1. A method for preparing quartz sand, characterized in that, Includes the following steps: 1) A mixture of chlorosilane, silicate ester and water is subjected to a hydrolysis reaction to generate a hydrolysate containing HCl and SiO2 nanoparticles; 2) Add alkali solution to the hydrolysate to make the pH of the system reach 8.5~11, and form a gel; 3) The gel is dried to obtain a loose SiO2 body; 4) The porous body is calcined to obtain quartz sand.

2. The preparation method according to claim 1, characterized in that, The chlorosilanes include at least one of silicon tetrachloride, trichlorosilane, dichlorosilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, hexachlorosilane, and methyldichlorosilane.

3. The preparation method according to claim 1 or 2, characterized in that, The silicate ester includes at least one of methyltrimethoxysilane, methyltriethoxysilane, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, pentyl orthosilicate, isopropyl orthosilicate, isobutyl orthosilicate, isoamyl orthosilicate, dimethyl orthosilicate, diethyl orthosilicate, and diisopropyl orthosilicate.

4. The preparation method according to any one of claims 1-3, characterized in that, The molar ratio of chlorosilane, silicate ester and water is 0.1~5:1~10:1~30, the reaction temperature is 40~90℃, the pressure is 0~0.5MPaG, the time is 1~5h, and the stirring rate is 50~400rpm.

5. The preparation method according to any one of claims 1-4, characterized in that, Step 1) also includes adding a surfactant to the hydrolysate.

6. The preparation method according to any one of claims 1-5, characterized in that, The alkaline solution includes at least one of ammonia, pyridine, ammonium carbonate solution, and ammonium bicarbonate solution; and / or, The alkaline solution is dropped at a rate of 0.5~5 kg / min, at a temperature of 40~90℃, and at a stirring speed of 50~400 rpm.

7. The preparation method according to any one of claims 1-6, characterized in that, The gel is dried at a temperature of 20~150℃, a pressure of -0.1~0.1MPaG, and a time of 5~20h.

8. The preparation method according to any one of claims 1-7, characterized in that, In step 4), the calcination includes a first stage calcination and a second stage calcination performed sequentially. The first stage calcination is carried out in air at 300-600°C for 10-20 hours, and the second stage calcination is carried out in HCl at 800-1600°C for 10-50 hours.

9. The preparation method according to claim 5, characterized in that, The surfactant includes at least one of PEG, Tween, fatty alcohol polyoxyethylene ether, and propylene glycol monooleate.

10. The preparation method according to claim 8, characterized in that, The second stage of roasting also includes the introduction of an inert gas.

Citation Information

Patent Citations

  • High-purity quartz sand and preparation method and application thereof

    CN110862091A

  • Preparation method of ultra-pure spherical quartz sand

    CN112551534A

  • 6N-grade large-particle quartz sand and preparation method thereof

    CN116375040A

  • Low-hydroxyl low-inclusion quartz sand as well as preparation method and application thereof

    CN119038562A

  • Synthetic sand purification method

    CN119160903A